2001
DOI: 10.1525/maq.2001.15.1.100
|View full text |Cite
|
Sign up to set email alerts
|

From Illness Narratives to Social Commentary: A Pirandellian Approach to “Nerves”

Abstract: The concept of "nerves" is an integral component of the language of distress found in a number of societies. Individuals, however, often extend its meaning well beyond the realm of suffering. In this article, I examine some Sicilian-Canadian uses of "nerves" from a Pirandellian perspective. This, I believe, gives us an insight into how people (1) make use of illness narratives to give meaning to their life experiences, and (2) attempt to influence the thought and behavior of significant others. In the process,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…In light of elders' responses to our questions about depression, we suggest that depression is a cultural and social construction and a form of communication (Migliore, 2001;Mills, 2000) often expressed through metaphor and embedded in a story that expresses a range of emotions, mental processes, and physical symptoms (Fernandez, 1974). Constructions of depression include folk beliefs about the causality, ontology, and treatment of depression, and are based in elders' cultural, ethnic, and religious traditions.…”
Section: Resultsmentioning
confidence: 99%
“…In light of elders' responses to our questions about depression, we suggest that depression is a cultural and social construction and a form of communication (Migliore, 2001;Mills, 2000) often expressed through metaphor and embedded in a story that expresses a range of emotions, mental processes, and physical symptoms (Fernandez, 1974). Constructions of depression include folk beliefs about the causality, ontology, and treatment of depression, and are based in elders' cultural, ethnic, and religious traditions.…”
Section: Resultsmentioning
confidence: 99%
“…Although significant anthropological attention has been given to the psychological and cultural context of physical illness in the global South (from "folk illness" to "culture-bound syndromes") (Carey 1993;Kleinman 1986;Migliore 2001), social scientists have also turned their ethnographic attention to medically unexplained illness in the global North (Barker 2005;Kilshaw 2010;Kroll-Smith and Floyd 1997;Nettleton 2006;Nettleton et al 2004). For example, anthropologist Joseph Dumit has described "contested, emerging illnesses" as "illnesses you have to fight to get" (2006) or "new socio-medical disorders" (2000) and has suggested that they are characterized by five features: chronicity, biomentality, therapeutic diversity, cross-linkage, and legal explosivity (2006:578).…”
Section: Medically Unexplained Illnesses and Competing Medical Epistementioning
confidence: 99%
“…With the disappearance of indigenous healers, increased reliance on bio-medicine, and the resulting stigma attached to folk illnesses and their traditional treatments (Nigenda et al 2001), an illness such as susto would have disappeared or been re-interpreted by Gregorians. These symptoms are common to other populations' general feelings of malaise and can encompass other folk illnesses (see, for example, the "nerves" literature: Low 1985Low , 1994Low and Davis 1989;Lock 1993;Davis and Guarnaccia 1989;Migliore 2001) and therefore could theoretically represent another folk illness rather than susto. In particular, Gregorians with less exposure to urban mestizo culture, as defined by Gregorians themselves, but nonetheless preferring biomedicine, would be more likely to express symptoms of a folk illness and label it as low/variable blood pressure.…”
Section: Understanding Low/variable Blood Pressure In Larger Sociostrmentioning
confidence: 99%